1991
DOI: 10.1007/bf01313484
|View full text |Cite
|
Sign up to set email alerts
|

Survey of mycosporine-like amino acid compounds in Antarctic marine organisms: Potential protection from ultraviolet exposure

Abstract: Abstract.To investigate the natural defenses of Antarctic marine organisms against exposure to ultraviolet (UV) radiation (280 to 320 nm), 57 species (1 fish, 48 invertebrates, and 8 algae) were collected during austral spring 1988 in the vicinity of Palmer Station (Anvers Island, Antarctic Peninsula) and were analyzed for the presence of mycosporine-like amino acids (MAAs), compounds that absorb UV radiation and may provide shielding from these biologically hazardous wavelengths. Nearly 90% of the 57 species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
329
1
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 465 publications
(349 citation statements)
references
References 30 publications
10
329
1
3
Order By: Relevance
“…Indeed previous surveys have reported MAA concentration based on single samples for each organism (e.g. Karentz et al, 1991;McClintock and Karentz, 1997) or a very low number of replicates (e.g. Bosch et al, 1994;Büdel et al, 1997;Teai et al, 1997;Xiong et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed previous surveys have reported MAA concentration based on single samples for each organism (e.g. Karentz et al, 1991;McClintock and Karentz, 1997) or a very low number of replicates (e.g. Bosch et al, 1994;Büdel et al, 1997;Teai et al, 1997;Xiong et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It might result from errors in the determination of K d , wavelengthdependent variation of m d or of the b/a ratio, or from absorption by other components, such as the photoprotective mycosporine-like amino acid pigments, MAAs. These pigments are produced by some phytoplankton and absorb most strongly between 300 and 360 nm [Karentz et al, 1991;Vernet and Whitehead, 1996]. Interactions of this nature could represent a limitation to the remote determination of CDOM absorption coefficients, since, in a phytoplankton bloom which produces a high concentration of MAAs, the relationships developed above might not apply.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds absorb UVR at a wavelength range between 310 nm and 360 nm and can be synthesized by many organisms [17][18][19][20]. Also many studies [21] have shown that they can be bioaccumulated through the diet by organisms at higher trophic levels that do not have the capacity of synthesis of them. The protective role of MAAs have been shown in previous studies (e.g.…”
Section: Introductionmentioning
confidence: 99%